Refractory Hypothyroidism Due to Improper Storage of Levothyroxine Tablets - Benvenga, Salvatore; Papi, Giampaolo; Antonelli, Alessandro (Frontiers in Endocrinology, 2017)
Context. A not negligible part of hypothyroid patients on levothyroxine therapy do not normalize serum thyrotropin concentrations. “Refractory hypothyroidism”, i.e. a condition characterized by persistently abnormal serum TSH levels despite adequate titration of L-T4 substitution therapy, requires biochemical and instrumental investigation, but no definite etiology is found in up to 15% of cases. Objective. To report patients presenting with refractory hypothyroidism with proven improper storage of levothyroxine tablets. Design. Patients on L-T4 substitution therapy referred to three Italian outpatient Clinics of Endocrinology between January 2013 and December 2015 for refractory hypothyroidism were investigated for levothyroxine tablet exposure to humidity, light and high temperature. Results. We report eight patients, accounting for approximately 1% of all hypothyroid patients and 5% of those with refractory hypothyroidism in our series. Careful anamnesis disclosed that these patients stored levothyroxine tablets inappropriately. Normalization of serum TSH concentrations was obtained in all cases by simply recommending to store the new levothyroxine tablets away from heat, light and humidity. Conclusions. Refractory hypothyroidism linked to improper storage of L-T4 tablets does exist, and might be an under-recognized entity. In addition to proper modalities of ingestion of L-T4 tablets, patients need to be instructed on proper modalities of storage, as well.